A Study on the effect of the Wind Catcher in Apartment Buildings - Ishikawa, Kotaro; Kurabuchi, Takashi; Kim, Jeongil (CLIMA 2022 conference, 2022)
In recent years, there has been growing emphasis on natural ventilation for energy conservation and intellectual productivity. However, in urban areas with a high building density, it is difficult to let in fresh outdoor air into the room, and installing a wind catcher (WC) is considered an effective solution. In this study, we conducted wind tunnel experiments and computational fluid dynamics (CFD) analysis to verify the ventilation-enhancing effects of installing WC in apartment buildings. Two models are used in this study. In the initial stages of wind tunnel testing and CFD analysis, we used a model without adjoining rooms to determine the correspondence of the wind tunnel test values to the CFD analysis values. Subsequently, CFD analysis was performed using the model with an adjacent room, and comparisons were made with the model without an adjacent room. Using the model with an adjacent room, we also studied the difference in the ventilation volume depending on the wind direction and ventilation volume with a single-sided opening. Consequently, we determined the following: 1.The pressure difference between the inlet and outlet openings was smaller in the model with an adjacent room than in the model without an adjacent room, and the ventilation volume was smaller. In other words, installing a WC in an apartment building can create a pressure difference, which is considered effective in promoting ventilation. 2.The WC works effectively for the wind flowing parallel to the opening.